If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + x = 10 + -2x Solving 1 + x = 10 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 1 + x + 2x = 10 + -2x + 2x Combine like terms: x + 2x = 3x 1 + 3x = 10 + -2x + 2x Combine like terms: -2x + 2x = 0 1 + 3x = 10 + 0 1 + 3x = 10 Add '-1' to each side of the equation. 1 + -1 + 3x = 10 + -1 Combine like terms: 1 + -1 = 0 0 + 3x = 10 + -1 3x = 10 + -1 Combine like terms: 10 + -1 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| -6x-15=58 | | ax+b+cx=d | | 2x^2-4=60 | | x^2+2x(0.4)=0.84 | | -x+2y+4z=-11 | | f(x)=x^2+13x+37 | | B=pn+pforn | | 12x+2=(7)2x-3 | | 6p^2+25x+4=0 | | y=.33(x-27) | | 2.75f=24.5 | | 5-6lnx=20 | | (3x-c)(x-3)=12 | | 5n^2=-5n+160 | | 7s+8l=180 | | 4x-2=3(2x+5)-31 | | 5x-20=2x | | x+8y=29 | | 2t^3+13t+15t=0 | | y=9x^2+x+7 | | 4(8x+10)=32x-8 | | 9k+27=0 | | 2+3(-1)/6+(-7)+1= | | 9x+15=9x-15 | | 7+2s-5=8s+20-4s | | 4600=k(30) | | 4v+23v+28=0 | | 2s+8l=120 | | x^4-5x^3-13x^2-7x=0 | | 14-2(3p+1)=5x-(x+21) | | 14-(-2)=10 | | 85+110+12x-1+11x+5=360 |